Knowledge and Experience of STIs Among Female Sexual Workers in an African Rural Community: The Impact of Community-based Interventions - Onoja, Ali Johnson; Shaibu, John; Sanni, Felix Olaniyi; Oguche, Daniel; Adamu, Imam; Abiodun, Paul Olaiya; Onoja, Sheila (Health Prospect, 2022)
Backgrounds: Sufficient knowledge of STIs is important in the prevention and control of HIV. This study compares the knowledge and experience of STIs among female sex workers (FSW) in a rural community with and without intervention. Methodology: The study is a quantitative study involving FSW in Bonny Kingdom. A structured questionnaire was used to obtain the demographics, knowledge and symptoms of STI. Data were analysed using SPSS version 25. Results: There were 261 respondents in the pre-intervention and 186 in post-intervention surveys. Knowledge of STIs was 86.6% in the pre-intervention and 97.3% in the post-intervention surveys. Knowledge of STI symptoms in women ranged from 23.7% to 32.5% in pre-intervention and 65.3 to 93.9% in post-intervention. Knowledge of STI symptoms in men ranged from 25.6%-37.9% in pre-intervention and 62.5%-93.8% in the post-intervention. In pre-intervention, 44.7% experienced STI symptoms within 12 months and 9.3% in the last two-months as compared to 6 3.2% and 1.1% in post-intervention survey. Conclusion: This study showed a significant reduction of STI among FSW due to interventions. Intervention is an important tool in the prevention and control of STIs and HIV in rural communities where there are limited and poor health facilities.